2010
DOI: 10.1007/s00253-010-2560-0
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the effect of medium-chain-length lactones on yeast membranes. Importance of the culture medium

Abstract: In hydrophobic compounds biotechnology, medium-chain-length metabolites often perturb cell activity. Their effect is usually studied in model conditions of growth in glucose media. Here, we study whether culture on lipids has an impact on the resistance of Yarrowia lipolytica to such compounds: Cells were cultured on glucose or oleate and submitted to gamma-dodecalactone. After a 60-min exposure to 3 g L(-1), about 80% of the glucose-grown cells (yeast extract peptone dextrose (YPD) cells) had lost their culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…This effect depends on the length of the apolar part of the lactone with dodecalactone being more toxic than shorter chain-length lactones . Moreover, it was shown recently that γ-dodecalactone provoked the depletion of ergosterol in a way similar to methyl-β-cyclodextrin and that depleted cells were more sensitive to the lactone shock (Ta et al 2010). …”
Section: Sensitivity Of Y Lipolytica To Amphiphilic Compounds and Mementioning
confidence: 97%
See 3 more Smart Citations
“…This effect depends on the length of the apolar part of the lactone with dodecalactone being more toxic than shorter chain-length lactones . Moreover, it was shown recently that γ-dodecalactone provoked the depletion of ergosterol in a way similar to methyl-β-cyclodextrin and that depleted cells were more sensitive to the lactone shock (Ta et al 2010). …”
Section: Sensitivity Of Y Lipolytica To Amphiphilic Compounds and Mementioning
confidence: 97%
“…With Y. lipolytica, it was shown that although the incorporation of oleyl moieties into the membrane made it more fluid, it also gave it a higher buffer capacity toward the incorporation of γ-dodecalactone. This was imputable to the location of the long-chain oleyl moieties into the membrane, fluidising both the polar edge and the apolar core of the membrane and modifying the polarity of the edge (Ta et al 2010). The presence of oleyl could thus reinforce the membrane against a toxic interdigitated phase transition which could be induced by the presence of short-chain compounds (Weber and De Bont 1996).…”
Section: Sensitivity Of Y Lipolytica To Amphiphilic Compounds and Mementioning
confidence: 97%
See 2 more Smart Citations
“…Whereas most laboratory strains were haploids strain, which could hardly be used in industrial production. Otherwise, when Yarrowia lipolytica grow on the medium that methyl ricinoleate as the only carbon source, the lactone had a marked effect on the membrane fluidity and the sterol concentration which are well known as important components in the regulation of membrane physiological properties (Ta et al 2010). The presence of increasing concentrations of copper in the growth medium may have influence on membrane integrity, accordingly affect the yields of c-decalactone.…”
Section: Fermentation Test and C-decalactone Analysismentioning
confidence: 99%